Materno-fetal outcomes in pre eclampsia in a rural hospital of Antananarivo Madagascar - Randriamahavonjy, Romuald; Tsifiregna, Rosa L.; Andrianirina, Zafitsara Z.; Andrianampanalinarivo, Hery R. (International Journal of Research in Medical Sciences, 2018)
Background: Pre-eclampsia is a human-pregnancy-specific disease defined as the occurrence of hypertension and significant proteinuria in a previously healthy woman on or after the 20th week of gestation. It is one of the leading causes of maternal and perinatal morbidity and mortality worldwide. The aim of this study is to determine the prevalence of pre-eclampsia and to evaluate its maternal and fetal outcomes in a rural area. Methods: This is a cross-sectional study carried out at the Bejofo Mahitsy hospital. It is a District Hospital Referral Center, which is located on the outskirts of the capital, 32 km from Antananarivo, Madagascar. This work was carried out during 24 months, from January 2014 to December 2016. We have included all hospitalized pregnant patients with SBP ≥140 or DBP ≥90mmHg, significant proteinuria> 300mg/24H with or without edema. Results: During this period, we recorded 97 cases of pre-eclampsia, frequency of 1.68%. The mean age of the parturient was 28 years old and 46.39% of the patients were primiparous. At the admission to the hospital, 37 (38,14%) did not show any particular signs. Concerning the severe high blood pressure, 47 pregnant patients (48,46%) had SBP greater than 160 mm Hg and 26 womens (26,80%) had DBP greater than 110 mm Hg. Caesarean section was the method of delivery widely adopted in 74.22 %. Maternal morbidity was represented by eclampsia in 21.65%, Retroplacentary Hematoma in 3% and HELLP syndrome in 4.12%. Fetal morbidity was important with 35% of premature newborns, 25.77% was small for gestational age and 12.37% was with neonatal asphyxia. Intra uterine fetal mortality was found in 11.34% and the perinatal mortality rate was 8.73%. Conclusions: There is a high frequency of pre-eclampsia in our setting and the consequences of pre-eclampsia for neonatal mortality and morbidity outcome are alarmingly high pre-eclampsia. Prevention necessarily involves quality prenatal follow-up such as screening, early and appropriate care of hypertension during pregnancy.